TEAM GAMES TOURNAMENT COOPERATIVE LEARNING STRATEGY AND LEARNING MOTIVATION ON STUDENT LEARNING OUTCOMES OF ISLAMIC RELIGIOUS EDUCATION SMP NEGERI 2 BABALAN LANGKAT REGENCY - Eka Dewi (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
This study aims to find out and stress: (1) the effect of learning strategieson the learning outcomes of Islamic Religious Education in Babalan StateJunior High School 2, Langkat Regency, (2) the effect of learningmotivation on learning outcomes of Islamic Religious Education inBabalan Middle School 2, Langkat Regency, and 3) the interaction betweenlearning strategies and learning motivation towards the learning outcomesof Babalan Middle School 2 Islamic Education in Langkat District. Thestudy was conducted at Babalan 2 Public Middle School, LangkatRegency. This type of research is quantitative with experimental researchmethods. The population in the study were all students of class VII (seven)SMP Negeri 2 Babalan District Langkat 2018/2019 which consisted of 5(five) classes. The sampling technique is done by cluster randomsampling. Data collection techniques are questionnaires and test results.Data analysis techniques used two-way variance analysis with asignificance level of α = 0.05. The results of the study are: (1) the averagelearning outcomes of Islamic Education students taught with the TGTcooperative learning strategy higher than the average learning outcomesof Islamic Religious Education students taught with expository learningstrategies, (2) the average learning outcomes of Islamic Education studentswith high learning motivation igher than the learning outcomes of IslamicEducation students with low learning motivation, and (3) there is aninteraction between learning strategies and learning motivation towardsthe learning outcomes of Islamic Education.